Web 2.0 Applications in Open Access Institutional Repositories of Asia - Khan, Aasif Mohammad; Loan, Fayaz Ahmad; Ahmad Andrabi, Syed Aasif (DESIDOC Journal of Library & Information Technology, 2022)
The primary purpose of the present study is to find out the adoption of Web 2.0 tools in social science repositories of Asian countries. Open access repositories were selected from OpenDOAR in the year 2021. Later, websites of all repositories were manually checked to identify the existence of Web 2.0 tools. The results revealed that Japan has established the maximum number of open access digital repositories in Asia, followed by Indonesia, Turkey, India, and China. The study shows that out of the total 101 social science institutional repositories found in these top five Asian countries, only 92 repositories were operational, and the rest weren’t accessible. From the operational repositories, 31.60 per cent (30) were Web 2.0 enabled, and 69.40 per cent (62) hadn’t incorporated Web 2.0 in their repositories. The highest number of Web 2.0 enabled repositories was found in Turkey, followed by Indonesia and China. Japan has the highest number of OA repositories but lags behind Turkey, Indonesia, and China in Web 2.0 enabled repositories. The least number of Web 2.0 enabled repositories were found in India among these countries. RSS feeds and Atom were the most used Web 2.0 tools in these institutional repositories.